Cerebral Microhemorrhages Detected by Susceptibility-Weighted Imaging in Amateur Boxers - Hasiloglu, Z.I.; Albayram, S.; Selcuk, H.; Ceyhan, E.; Delil, S.; Arkan, B.; Baskoy, L. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: SWI is a new technique for evaluating diffuse axonal injury associated with punctate hemorrhages. The aim of our study was to determine the prevalence of cerebral microhemorrhages in amateur boxers compared with nonboxers by using SWI and to evaluate the sensitivity of SWI compared with T2 FSE and T2*GE sequences. MATERIALS AND METHODS: We performed cranial MR imaging with a 1.5T scanner in 21 amateur boxers and 21 control subjects. The study protocol included conventional MR images, T2 FSE, T2*GE, and SWI sequences. The proportions of boxers and controls having CSP, DPVS, cerebral atrophy, cerebellar atrophy, ventricular dilation, PSWMD, and microhemorrhages were computed and were compared by using the χ2 test of proportions. The relationship between microhemorrhages and boxing-related covariates was assessed by using the Wilcoxon rank sum test. The association between the categories was tested by using the Fisher exact test. RESULTS: Using SWI, microhemorrhages were found in 2 (9.52%) of 21 boxers. The microhemorrhages were not visible on T2 FSE or T2*GE images. The proportion of subjects with microhemorrhages did not differ significantly between the boxers and control subjects (χ2 = 0.525, df = 1, P = .4688). The prevalence of CSP and DPVS was significantly higher in the boxers than in the control subjects. CONCLUSIONS: More microhemorrhages were detected in amateur boxers than in controls, but this difference was not statistically significant. Aactive boxerCSPcavum septum pellucidumDAIdiffuse axonal injuryDPVSdilated perivascular spaceGEgradient-echoKOknockoutMHmicrohemorrhagesMMSEMini-Mental State ExaminationPSWMDperiventricular and subcortical white matter diseaseRretired boxerSEspin-echoSWIsusceptibility-weighted imagingT2 FSET2-weighted fast spin-echoT2*GET2*-weighted GETBItraumatic brain injury